Comprehensive miRNA Analysis of Human Umbilical Cord-Derived Mesenchymal Stromal Cells and Extracellular Vesicles - Xiang-yu Zou; Yongjiang Yu; Sihao Lin; Liang Zhong; Jie Sun; Guangyuan Zhang; Yingjian Zhu (Karger Publishers, 2018)
Background/Aims: Mesenchymal stromal cells (MSCs) participate in the tissue-specific repair of many different organs, especially the kidney. Their effects are primarily mediated by the paracrine release of factors including extracellular vesicles (EVs), which are composed of micro-vesicles and exosomes. The corresponding microRNAs (miRNAs) of EVs are considered important for their biological functions. Methods: MSCs were cultured from the human umbilical cord, and EVs were isolated from the medium. The expression levels of miRNAs in MSCs and EVs were determined by microarray analysis, and gene ontology (GO) was used to analyze the functions of their target genes. Results: MSCs and EVs had similar miRNA expression profiles, with the exception of a small number of selectively enriched miRNAs. GO analysis indicated that, unlike MSCs, the target genes of EV-enriched miRNAs were associated with calcium channel regulation and cell junction activities, which may indicate that MSC and EVs have different regulatory properties. Angiogenesis, oxidative stress, and inflammatory signaling pathways related to the repair of renal injury were also analyzed, and EV-enriched miRNAs targeted genes associated with oxidative stress, T cell activation, and Toll-like receptor signaling. The miRNAs enriched in both MSCs and EVs targeted different genes in signaling pathways regulating angiogenesis and chemokine release. Conclusion: MSCs and their EVs shared similar miRNA component, and some selectively enriched miRNAs observed in MSCs and EVs may affect different target genes through some specific signaling pathways.